2019
DOI: 10.3390/ijms20071742
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Virtual Screening and In Vitro Evaluation of New Trypanosoma cruzi Cruzain Inhibitors

Abstract: Chagas disease (CD), or American trypanosomiasis, causes more than 10,000 deaths per year in the Americas. Current medical therapy for CD has low efficacy in the chronic phase of the disease and serious adverse effects; therefore, it is necessary to search for new pharmacological treatments. In this work, the ZINC15 database was filtered using the N-acylhydrazone moiety and a subsequent structure-based virtual screening was performed using the cruzain enzyme of Trypanosoma cruzi to predict new potential cruzai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Higher AUC values in the ROC curves infer greater sensitivity of WT-pharma and MT-Pharma in retrieving actives, and specificity for ignoring inactives [ 48 , 49 ]. Using ZINC 15 , Mayorga et al found a high number of compounds when they utilized a small fragment of the original structure [ 50 ]. In our study, to explore analogs of MTX, we used the full structure of MTX and selected ‘in vitro’, ‘in vivo ‘and ‘clean’ options in the section of ‘subsets’, which resulted in the generation of only 32 analogous compounds ( Table S1 .…”
Section: Discussionmentioning
confidence: 99%
“…Higher AUC values in the ROC curves infer greater sensitivity of WT-pharma and MT-Pharma in retrieving actives, and specificity for ignoring inactives [ 48 , 49 ]. Using ZINC 15 , Mayorga et al found a high number of compounds when they utilized a small fragment of the original structure [ 50 ]. In our study, to explore analogs of MTX, we used the full structure of MTX and selected ‘in vitro’, ‘in vivo ‘and ‘clean’ options in the section of ‘subsets’, which resulted in the generation of only 32 analogous compounds ( Table S1 .…”
Section: Discussionmentioning
confidence: 99%
“…12 , 22 The functional groups of the subsets divided by the chemical family resemble those in the previously reported local models shown in Table 1 . Moreover, current efforts in the search for cruzain inhibitors focus on the design and optimization of particular chemotypes, including imidazoles and benzimidazoles, 9 , 86 , 87 N -acyldhydrazones, 88 imides, 89 vinyl peptidomimetics, 2 , 11 , 90 oxadiazoles, 2 , 11 , 91 and triazoles, 10 among others. Molecules that belong to these chemical groups are part of our curated modeling database.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in the field of malaria research, recent works have focused on the application of an integrative multi-kinase approach ( Lima et al, 2019 ), the identification of malarial allosteric modulators combining molecular dynamics simulations and dynamic residue network analysis ( Amusengeri et al, 2019 ), the ensemble of ligand-based computational models for virtual screening of falcipain-2 inhibitors ( Alberca et al, 2019 ), and quantitative structure-activity relationships (QSAR) for the study of N-myristoyltransferase inhibitors ( Santos-Garcia et al, 2018 ). Regarding ChD, a wide range of in silico approaches have been reported to discover protein inhibitors with a special focus on cruzipain ( Palos et al, 2017 ; Dos Santos et al, 2018 ; Herrera-Mayorga et al, 2019 ). Following with AAT, several works have reported the use of computational tools to accelerate the search for inhibitors of different targets ( Latorre et al, 2016 ; Di Pisa et al, 2017 ; Kimuda et al, 2019 ; Zacharova et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%